1992
DOI: 10.1007/bf03348807
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of hyperthyroidism in multinodular goiter after long-term drug therapy: A comparison with Graves’ disease

Abstract: The chance of permanent remission after prolonged drug therapy was investigated in 41 patients with toxic multinodular goiter. For purposes of comparison a group of 41 patients with Graves' disease was also studied. After euthyroidism was achieved all patients received a combination of thionamide and thyroxine for at least 12 months. The minimum follow-up period was 2 yr. Relapse of thyrotoxicosis occurred in 95.1% of patients with toxic multinodular goiter and 34.1% of patients with Graves' disease (p < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…The main factor in the development of hyperthyroidism is time, with TMG being the final phase in its evolution, while nodules acquire autonomy. 1,2,[18][19][20] According to our multivariate analysis, the most characteristic feature of TMG is its greater evolution time. The long preoperative evolution time explains why more than 40% of our patients with TMG had an associated intrathoracic component and a high incidence of compressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factor in the development of hyperthyroidism is time, with TMG being the final phase in its evolution, while nodules acquire autonomy. 1,2,[18][19][20] According to our multivariate analysis, the most characteristic feature of TMG is its greater evolution time. The long preoperative evolution time explains why more than 40% of our patients with TMG had an associated intrathoracic component and a high incidence of compressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Surgery is the treatment of choice because it achieves fast and permanent relief of symptoms. 3,4 Most studies have shown that hyperthyroidism produces the highest rate of complications, in the form of hypoparathyroidism (3.8%-14%) or recurrent lesions (4%-13%), [5][6][7] Moreover, it usually occurs in older patients, who often have high surgical risk, which is why alternative nonsurgical therapy is being sought.…”
Section: Introductionmentioning
confidence: 99%
“…All three therapeutic options would be effective in the treatment of patients with Graves’ disease, whereas patients with toxic adenoma or toxic multinodular goitre should have either radioactive iodine therapy or surgery, since these patients rarely go into remission. 54 In patients with toxic nodular goitre, ATDs are generally used to restore euthyroidism before definitive treatment with surgery or radioactive iodine, and infrequently used as long-term treatment when the other two therapies are contraindicated or the patient has a short life expectancy.…”
Section: Treatmentmentioning
confidence: 99%
“…Three treatment options are available for hyperthyroidism: antithyroid drugs, radioiodine-131 (I-131), and thyroidectomy. Antithyroid drugs are highly effective in controlling hyperthyroidism, but are known to have relapse rates up to 70% after 1 year treatment in Graves' disease, whereas toxic multinodular goiter rarely resolves with drug treatment (4). Radioiodine treatment has been widely used as a definitive treatment of hyperthyroidism for over 60 years and has proven to be safe and costeffective (5).…”
Section: Introductionmentioning
confidence: 99%